Is cestode infection intensity associated with decreased body condition in the Eurasian woodcock Scolopax rusticola?. Issue 1 (26th January 2017) - Sánchez-García, C.; Harris, E.; Deacon, A.C.; Bray, R.; Hoodless, A.N.
Abstract: The Eurasian woodcock Scolopax rusticola is a widespread woodland specialist and a widely harvested quarry species throughout its European wintering areas, including Britain. Woodcock are prone to cestodiasis, but prevalence levels and possible effects on body condition remain under-studied. We studied the prevalence, abundance and intensity of cestodiasis in 161 woodcock harvested in four British regions in December and January during two consecutive winters (2013/14 and 2014/15). Cestodiasis prevalence was 90%, and there was no difference in prevalence between birds harvested in Cornwall, Wessex, East Anglia and Scotland. High prevalence levels were explained by the fact that earthworms (Lumbricidae) are intermediate hosts for some cestode species and also the most important dietary component of woodcock. The distribution of cestodiasis in woodcock was aggregated, such that when using the total length of cestodes per sample to measure abundance, 65% of the birds had less than 80 cm. Cestodiasis abundance varied between sexes across regions but the intensity was not affected by region, sex, age or their interactions. The intensity of cestodiasis was positively correlated with fresh weight and pectoral mass, while no significant correlation was found with the abdominal fat pad. Our results suggest that, despite high prevalence levels and intensity of cestodiasis in woodcock, host body condition is not significantly affected and hence it is unlikely that cestodiasis has a major effect on woodcock population dynamics.